Learning in Lockdown: Teaching Human Rights Practice During the COVID-19 pandemic. (12th March 2022) - Roda, Claudia; Perry, Susan
Abstract: This article explores the authors' university course on 'Human Rights and Digital Technology', designed to engage students in a holistic assessment of the application of international human rights law to the digital universe. In addition to the intellectual premises of our course, this article examines the notable shift in teaching practice during the start of the Covid-19 pandemic, as the authors moved from classroom to online instruction. We argue that during the pandemic many students experienced the loss of equal access to higher education based on merit or capacity, a human right guaranteed by the Universal Declaration and the International Covenant on Economic, Social and Cultural Rights. In fact, students recognized how online education, at least in this specific context, may have exacerbated social and economic differences. This article provides the analysis of a small survey of our students' perceptions of online learning in the middle of a global pandemic. Based on the authors' observations and survey results, our article points to three salient factors that affected the quality and fairness of online education during the lockdown period: the absence of in-person, experienced human feedback to hone critical thinking; access (or lack thereof) to functioning technology; and compromised student attention. We highlight several lessons learned from this experience, and how a human rights framework may help both professors and students identify the conditions under which online learning is more likely to be successful and to guarantee equal access to higher education.